Spectral estimator effects on accuracy of speed-over-ground radar - Mohd Shariff, Khairul Khaizi; Zainuddin, Suraya; Abdul Aziz, Noor Hafizah; Abd Rashid, Nur Emileen; Zalina Zakaria, Nor Ayu (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Spectral estimation is a critical signal processing step in speed-over-ground (SoG) radar. It is argued that, for accurate speed estimation, spectral estimation should use low bias and variance estimator. However, there is no evaluation on spectral estimation techniques in terms of estimating mean Doppler frequency to date. In this paper, we evaluate two common spectral estimation techniques, namely periodogram based on Fourier transformation and the autoregressive (AR) based on burg algorithm. These spectral estimators are evaluated in terms of their bias and variance in estimating a mean frequency. For this purpose, the spectral estimators are evaluated with different Doppler signals that varied in mean frequency and signal-to-noise ratio (SNR). Results in this study indicates that the periodogram method performs well in most of the tests while the AR method did not perform as well as these but offered a slight improvement over the periodogram in terms of variance.